2013
DOI: 10.1097/mca.0b013e32835b6798
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of infarct size by speckle tracking echocardiography in patients with anterior myocardial infarction

Abstract: STE seems to be a very promising tool in the prediction of infarct size in patients with anterior STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Our study confirmed GLS’s value as a marker of infarct size in AMI patients, as evaluated by CMR at 3 months. We studied strain parameters in the three main axes (radial, longitudinal, and circumferential), whereas most other published studies were chiefly focused on longitudinal strain alone [36]. Reproducibility and feasibility of GLS have been well-established in the AMI setting [5], [6], [34], [35], [39], which underlines the parameter’s value as a prognostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed GLS’s value as a marker of infarct size in AMI patients, as evaluated by CMR at 3 months. We studied strain parameters in the three main axes (radial, longitudinal, and circumferential), whereas most other published studies were chiefly focused on longitudinal strain alone [36]. Reproducibility and feasibility of GLS have been well-established in the AMI setting [5], [6], [34], [35], [39], which underlines the parameter’s value as a prognostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Our observed associations between strain and MI size build upon prior studies conducted in smaller cohorts. Among 39 patients with anterior MI, Grabka et al reported GLS to correlate with CMR‐evidenced MI size ( r = .68, P = .001). That study, however, compared echo (performed 6 days post‐MI) to CMR performed 3 months afterward, prohibiting direct comparisons of imaging tests performed at near identical post‐MI time points.…”
Section: Discussionmentioning
confidence: 82%
“…[9][10][11] Strain has also been shown to yield improved agreement with volumetric chamber quantification as provided by well-validated techniques such as CMR. 12,13 Pilot studies have shown global strain to moderately correlate with MI size, 14,15 although these studies have been limited by small sample size and wide variations in interval between echo and CMR. Moreover, regional strain impairment has yet to be tested against CMR-quantified regional MI size and functional indices.…”
Section: Introductionmentioning
confidence: 99%
“…GLS, GCS or GRS was not different between patients with or without LV remodeling. The association between GLS and infarct size has been studied recently [2327]. Sjoli et al investigated GLS after revascularization in 39 patients with STEMI and treated with thrombolysis [26].…”
Section: Discussionmentioning
confidence: 99%